STUDI ETNOBOTANI TUMBUHAN OBAT SUKU “TOPO UMA” DI DESA Oo PARESE KECAMATAN KULAWI SELATAN KABUPATEN SIGI SULAWESI TENGAH - Christina Yulia; Fahri Fahri; Ramadhanil Pitopang (Biocelebes, 2017)
Research on "The ethnobotanical study of medicinal plants of Topo Uma Tribe in Oo Parese village Kulawi district Central Sulawesi has been conducted from August to October 2014. This study aimed to obtain information about the kinds of plants are utilized as medicine, organ herbs used, the type of disease being treated and how it is used by Uma Topo tribe in the village of Oo parese.  The research method was a survey method to obtain quantitative and qualitative data. A total of 41 (forty-one) respondents including traditional leaders, shaman/"sando", nurses and local communities in semi-structured interview to obtain the necessary data. The result showed there were  32 species of plants are utilized as a medicinal plant. Plant organ was used such as leave, fruit, stem, bark, secd and root. There were some deaseas can be treatied like. Chronic desease, by different kind of application method, i.e mashed, squeezed, smeared used as fresh vegetables and stewed before served.